Impact of obesity on male urethral sling outcomes - Monn, M. Francesca; Jarvis, Hannah V.; Gardner, Thomas A.; Mellon, Matthew J. (Therapeutic advances in urology, 2020)
Background: The impact of obesity on AdVance male urethral sling outcomes has been poorly evaluated. Anecdotally, male urethral sling placement can be more challenging due to body habitus in obese patients. The objective of this study was to evaluate the impact of obesity on surgical complexity using operative time as a surrogate and secondarily to evaluate the impact on postoperative pad use. Methods: A retrospective cohort analysis was performed using all men who underwent AdVance male urethral sling placement at a single institution between 2013 and 2019. Descriptive statistics comparing obese and non-obese patients were performed. Results: A total of 62 patients were identified with median (IQR) follow up of 14 (4–33) months. Of these, 40 were non-obese and 22 (35.5%) were obese. When excluding patients who underwent concurrent surgery, the mean operative times for the non-obese versus obese cohorts were 61.8 min versus 73.7 min (p = 0.020). No Clavien 3–5 grade complications were noted. At follow up, 47.5% of the non-obese cohort and 63.6% of the obese cohort reported using one or more pads daily (p = 0.290). Four of the five patients with a history of radiation were among the patients wearing pads following male urethral sling placement. Conclusion: Obese men undergoing AdVance male urethral sling placement required increased operative time, potentially related to operative complexity, and a higher proportion of obese compared with non-obese patients required postoperative pads for continued urinary incontinence. Further research is required to better delineate the full impact of obesity on male urethral sling outcomes.